The Psychometric Properties of the Norwegian version of Eyberg Child Behavior Inventory (ECBI) - Reedtz, Charlotte; Martinussen, Monica (PsykTestBarn, 2011)
Description: The Eyberg Child Behavior Inventory (ECBI) was developed in the US during the 1970s (Eyberg & Ross, 1978) as a parent rating scale to assess behavior problems in children aged 3-16 years. ECBI was translated from English into Norwegian by Willy-Tore Mørch, affiliated with the Arctic University of Norway. The American Psychological Assessment Resources (PAR) distributes licenses needed to use the inventory. The ECBI can be employed as a tool for screening, for clinical use, as well as for research purposes. It provides a list of 36 problem behaviors commonly reported by parents. The inventory assesses behavior on two dimensions: 1) the frequency of the behavior; 2) whether parents consider it a problem. The frequency ratings range from 1 (never) to 7 (always), and are summed up to arrive at an overall problem behavior Intensity Score, ranging from 36 to 252. The problem identification assessment contains questions that require a yes/no response from parents/caregivers: “Is this behavior a problem for you?” The total Problem Score ranges from 0 to 36, and is calculated by summing up the number of problems indicated by the parents. Intensity Scale scores are used to evaluate the child’s behavior, whereas Problem Scale scores are utilized to evaluate the special challenges a child’s behavior poses to primary caregivers. It takes about 10-15 minutes to complete the ECBI. No special certification is required in order to administer the ECBI, except test-specific competence. Literature search: A total of 12 studies were included in this systematic review; 11 Norwegian studies and one Swedish. These studies were conducted with children aged 4-9 years in both clinical and general populations. Psychometrics: Psychometrical data consisted of mean values, standard deviations in representative norms groups, subgroups and clinical samples, as well as internal consistency reliability and explorative factor analyses. Konklusjon: The ECBI has very good reliability as well as Norwegian norms from a representative sample. Some evidence lends support to the construct validity of the test.